(untitled) (New York, 2013)
Everyone’s an Author focuses on writing as it really is today―with words, images, and sounds, in print and online―and encourages students to see the connections between their everyday writing and academic writing. It covers the genres college students need to learn to write―and teaches them to do so across media. It bridges the gap between Facebook and academic writing, showing how the strategies students use instinctively in social media can inform their academic writing. And it provides a strong rhetorical framework that guides students in the decisions they need to make as authors today.
Keywords: Viết báo cáo,Report writing